Secretariat - Nack, William (New York : Hyperion, 2010)
"In 1973, Secretariat, the greatest champion in horse- racing history won the Triple Crown. He still holds the record for the fastest times in both the Kentucky Derby and the Belmont Stakes. The tale of "Big Red" is an enduring classic, more than thirty years after its initial publication"--Back cover
Keywords: Secretariat (Race horse); Race horses -- United States -- Biography